1990
DOI: 10.1002/neu.480210207
|View full text |Cite
|
Sign up to set email alerts
|

Development and survival of thoracic motoneurons and hindlimb musculature following transplantation of the thoracic neural tube to the lumbar region in the chick embryo: Anatomical aspects

Abstract: Thoracic spinal cord transplanted to the lumbar region at the time of neural tube closure in the chick embryo survives and initially differentiates normally similar to in situ thoracic cord. Normal numbers of motoneurons are produced that innervate the host hindlimb musculature. In control thoracic cord approximately 70% of the motoneurons are lost by normal cell death between embryonic day (E) 6 and E11-E12. By contrast, the transplanted thoracic cord loses only about 30% of the motoneurons during this period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 51 publications
(44 reference statements)
3
26
0
Order By: Relevance
“…This is not surprising, because thoracic spinal cord contains only medial motor column, but not LMC, motoneurons. Together, these findings are consistent with previous studies showing that the phenotype and target specificity of sensory neurons are more plastic than motoneurons (McMahon and Gibson, 1987;Wenner and Frank, 1995;Scott, 1999, 2002) and that innervation of limb muscles does not convert thoracic motoneurons to LMC neurons (O'Brien and Oppenheim, 1990;Turney et al, 2003).…”
Section: Regulation Of Er81 In Sensory Neurons and Thoracic Motoneuronssupporting
confidence: 92%
“…This is not surprising, because thoracic spinal cord contains only medial motor column, but not LMC, motoneurons. Together, these findings are consistent with previous studies showing that the phenotype and target specificity of sensory neurons are more plastic than motoneurons (McMahon and Gibson, 1987;Wenner and Frank, 1995;Scott, 1999, 2002) and that innervation of limb muscles does not convert thoracic motoneurons to LMC neurons (O'Brien and Oppenheim, 1990;Turney et al, 2003).…”
Section: Regulation Of Er81 In Sensory Neurons and Thoracic Motoneuronssupporting
confidence: 92%
“…at later stages a chemically-mediated mismatch between nerve and muscle involving cell-cell interactions and the loss of synaptic stability may result in an uncoupling that leads to the observed regression of both nerve and muscle. Alternatively, owing to differences in number or type, thoracic motoneurons may be unable to provide sufficient innervation or trophic support to sustain the development of the rapidly developing limb muscles during the last half of the incubation period (cf., O'Brien and Oppenheim, 1990). Another possibility that we do not favor, but cannot exclude, is that eventually limb muscles fail to provide appropriate trophic support for nonlimb motoneurons resulting in motoneuron regression which in turn leads to muscle degeneration.…”
Section: Discussionmentioning
confidence: 91%
“…Manipulations of motor neuronal positioning, through inversions or rostrocaudal shifts of the neural tube (Lance-Jones and Landmesser, 1980Landmesser, , 1981bO'Brien and Oppenheim, 1989), or of limb targets, through transplant of supernumerary limbs Whitelaw and Hollyday, 1983a), limb bud rotations (Ferns and Hollyday, 1993;Whitelaw and Hollyday, 1983b) and limb bud ablations (Shorrey, 1909;Barron, 1948;Hamburger and O'Keefe, 1944;Whitelaw and Hollyday, 1983c;Tosney and Landmesser, 1984), have revealed that there are both permissive and instructive signals in the periphery that motor axons use to be guided to their correct targets. These experiments have yielded the model that local guidepost signals within the limb mesenchyme are used by motor axons to navigate.…”
Section: Specification Of Motor Axon Pathfindingmentioning
confidence: 98%